Turbot reovirus (SMReV) genome encoding a FAST protein with a non-AUG start site - Zhang Qi-Ya; Pei Chao; He Li-Bo; Ke Fei (BMC Genomics, 2011)
Abstract Background A virus was isolated from diseased turbot Scophthalmus maximus in China. Biophysical and biochemical assays, electron microscopy, and genome electrophoresis revealed that the virus belonged to the genus Aquareovirus , and was named Scophthalmus maximus reovirus (SMReV). To the best of our knowledge, no complete sequence of an aquareovirus from marine fish has been determined. Therefore, the complete characterization and analysis of the genome of this novel aquareovirus will facilitate further understanding of the taxonomic distribution of aquareovirus species and the molecular mechanism of its pathogenesis. Results The full-length genome sequences of SMReV were determined. It comprises eleven dsRNA segments covering 24,042 base pairs and has the largest S4 genome segment in the sequenced aquareoviruses. Sequence analysis showed that all of the segments contained six conserved nucleotides at the 5' end and five conserved nucleotides at the 3' end (5'-GUUUUA --- UCAUC-3'). The encoded amino acid sequences share the highest sequence identities with the respective proteins of aquareoviruses in species group Aquareovirus A. Phylogenetic analysis based on the major outer capsid protein VP7 and RNA-dependent RNA polymerase were performed. Members in Aquareovirus were clustered in two groups, one from fresh water fish and the other from marine fish. Furthermore, a fusion associated small transmembrane (FAST) protein NS22, which is translated from a non-AUG start site, was identified in the S7 segment. Conclusions This study has provided the complete genome sequence of a novel isolated aquareovirus from marine fish. Amino acids comparison and phylogenetic analysis suggested that SMReV was a new aquareovirus in the species group Aquareovirus A. Phylogenetic analysis among aquareoviruses revealed that VP7 could be used as a reference to divide the aquareovirus from hosts in fresh water or marine. In addition, a FAST protein with a non-AUG start site was identified, which partially contributed to the ...